Features of the formation of intercultural competence of foreign students in intercultural communication - Sadenova А.Е.; Aitbayeva Б.М.; Karybaeva С.Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The present article will focus on the relevance of the problem of intercultural communication in the educational process. In the educational process, it is necessary to take into account that if foreign students learn about the culture of the country, the educational process will be successful. The purpose of the article discusses the features of the formation of intercultural competence of foreign students in teaching and intercultural communication. It is important to teach students to see differences between cultures, to understand the characteristics of another culture, to overcome stereotypes, and to master speech etiquette, which generates trust and respect for another culture and allows them to feel confident in communication. The analysis of theoretical works is carried out. The practical significance of the work is also discussed. This material can be used as an application in the study of the problem of the formation of cultural competence in cultural communication, which is currently relevant both in the field and in language learning.